2020
DOI: 10.1097/md.0000000000022727
|View full text |Cite
|
Sign up to set email alerts
|

Integration of gene profile to explore the hub genes of lung adenocarcinoma

Abstract: Background: Lung cancer is a leading cause of morbidity diseases worldwide, but the key mechanisms of lung cancer remain elusive. This study aims to integrate of GSE 118370 and GSE 32863 profile and identify the key genes and pathway involved in human lung adenocarcinoma. Methods: R software (RStudio, Version info: R 3.2.3, Forrester, USA) were utilized to find the differentially expressed genes. All the differentially expressed genes were analyzed by gene ontology, kyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Recent years, with the progress of genome research and the development of modern biotechnology, a large amount of biological data has been accumulated, which leads to the unprecedented development of bio-information analysis 16 . More and more natural product pharmacology is looking for researching direction from bioinformatics and network pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years, with the progress of genome research and the development of modern biotechnology, a large amount of biological data has been accumulated, which leads to the unprecedented development of bio-information analysis 16 . More and more natural product pharmacology is looking for researching direction from bioinformatics and network pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described as a hub gene or a candidate biomarker in different cancer types. Hua et al [ 50 ] reported in their study that GNG11 acts as a hub gene in lung adenocarcinoma. Moreover, Shi et al [ 51 ] observed that GNG11 was downregulated in lung cancer, and low expression of GNG11 was associated with worse OS for female lung cancer patients who never smoked.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on P4HB in lung cancer mainly focused on bioinformatics analysis. P4HB was overexpressed in NSCLC tissues compared to adjacent normal tissues [68][69][70][71]. High expression of P4HB was associated with worse prognosis of LUAD patients [71].…”
Section: P4hb and Lung Cancermentioning
confidence: 99%